Identification of ectoparasite on tilapia (Oreochromis niloticus) along Coastal Road Brgy. La Huerta, Paranaque City from September 2004 to Janaury 2005 - Garcia, Anna Victoria Gob. 4 0 16 (2005)
ABSTRACT
Thesis (B.S. Biology) Pamantasan ng Lungsod ng Maynila, 2005.
This study is about the Identification of Ectoparasites on tilapia (oreochromis niloticus) from September 2004 to January 2005 with a month interval per sampling parasitological examinations.
Thirty samples were bought fishermen at the Fisherman's Wharf, Brgy. La Huerta, Parañaque City each month. Specimens were kept alive by using an aerator. Diagnosis was done following the procedures by Z. Kabata. The physico-chemical factors were also measured by the researcher. The temperature was taken using a laboratory thermometer. A pH was used for determining the pH values and Titration method was used for the amount of dissolved oxygen.
Two species of ciliated protozoan parasites were identified. Trichodina domerguei was found mostly infesting the gills while Cryptocatyon irritans was infesting the skin and sacles of the specimen. The physico-chemical factors were correlated with the number of ectoparasites found infecting the fish. Temperature had a perfect relationship with the occurrence of parasites, the pH had a moderate correlation and the dissolved oxygen had a very high correlation.
5
Keywords: 2 -- 0; 6; 0; 20